Well-Being: a proposal research on Gestalt therapy efficacy - 1 Alessandro Cini, 1 Silvio Oliva,1 Giovanni Paolo Quattrini (Phenomena Journal)
What happens during a psychotherapy treatment is something complex and difficult to describe. What can be expected is that the client comes to experience a higher quality of his life compared to the beginning of his journey. The aim of this paper is to introduce a research proposal to monitorate and to value the dynamics of well-being as perceived by the client along the psychotherapeutic relationship, in order to highlight the efficacy of Gestalt therapy in this way. We designed a longitudinal experimental framework using a qualitative and phenomenological-existential methodology. We propose a combinatory use of a self-assessment scale to investigate the well-being construct (an italian adaptation of Psychological Well-being scale) and the text analysis according to the guidelines suggested by the existential phenomenological method. The sample will be of 50 patients followed by phenomenological existential Gestalt psychotherapists. The data will be taken every 2 months (8 individual therapeutic sessions) from the beginning to the end of psychotherapy treatment (when the patient, in agreement with the therapist, decide to end the therapeutic relationship). In addition to the temporal dynamics of wellbeing, we will analyze the distributions and correlations between the classical six dimensions emerging from the Psychological Well-being and some personal factors collected through a sociodemographic card defined at hoc.